Isolation and identification of foodborne pathogen in chicken dishes from selected stall around Serdang area - Ahmad Jailani, Nur Maisarah (2015)
Everyone need food. But, due to the improper handling during the preparation of the food, it may lead to foodborne illness. Foodborne illness already become one of the major issues worldwide because not only it gives bad effect to the health problem, it may also give a negative impact towards economy. This illness can be transmitted during the intake of food that contain sufficient number of foodborne pathogen. In this study, two cooked chicken dishes were collected from different randomly chosen food stalls in Serdang area. The samples are chicken cooked in coconut gravy and chicken cooked with chili paste. The convential method were used to analyse the food samples for foodborne pathogen. The identification of unknown bacteria isolates were done by using 13 different biochemical tests. From a total of 25 isolates, four were detected as Bacillus cereus, Corynebacterium xerosis, Micrococcus luteus and Enterobacter aerogenes. From a total of four organisms detected, two of them were foodborne pathogens; Bacillus cereus and Enterobacter aerogenes.